2021
DOI: 10.24036/pakar.v18i2.222
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Differentiated Learning Strategies to Increase Learning Concentration of Children with Learning Difficulties

Abstract: Penelitian ini dilakukan berdasarkan permasalahan yang ditemukan di SDN 17 Jawa Gadut Padang. Hasil permasalahan yang ditemukan adalah adanya seorang anak yang teridentifikasi kesulitan belajar siswa tersebut memiliki permasalahan pada tingkat konsentrasinya yang rendah. Penelitian ini bertujuan untuk meningkatkan konsentrasi belajar pada siswa berkesulitan belajar di SDN 17 Jawa Gadut Padang dengan menggunakan strategi pembelajaran berdiferensiasi. Metode yang digunakan dalam penelitian ini adalah single subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…14 The Effectiveness of Differentiated Learning Strategies to Increase the Learning Concentration of Children with Learning Difficulties [17] Differentiated learning strategies design variations of learning that is considered to be interesting by combining types of children's learning styles in learning topics so that children are focused and interested in learning, from overall data analysis, analysis of data under conditions and analysis of data between conditions shows that there is an increasing concentration of learning in children with learning difficulties. From the results of the acquisition data, the differentiation learning strategy has an effect so that it can improve the learning concentration of children with learning difficulties (continued) Differentiated Instruction accommodates each student in accordance to their level of ability thus it gives motivation towards high school to be more enthusiastic in exhibiting their maximum performance in their learning process as the learning materials are also deemed easier to be understood.…”
Section: Resultsmentioning
confidence: 99%
“…14 The Effectiveness of Differentiated Learning Strategies to Increase the Learning Concentration of Children with Learning Difficulties [17] Differentiated learning strategies design variations of learning that is considered to be interesting by combining types of children's learning styles in learning topics so that children are focused and interested in learning, from overall data analysis, analysis of data under conditions and analysis of data between conditions shows that there is an increasing concentration of learning in children with learning difficulties. From the results of the acquisition data, the differentiation learning strategy has an effect so that it can improve the learning concentration of children with learning difficulties (continued) Differentiated Instruction accommodates each student in accordance to their level of ability thus it gives motivation towards high school to be more enthusiastic in exhibiting their maximum performance in their learning process as the learning materials are also deemed easier to be understood.…”
Section: Resultsmentioning
confidence: 99%
“…The third finding shows that differentiated learning is better and more effective in increasing student interest in learning and learning outcomes.The application of differentiated learning can improve learning outcomes,by attracting children's attention while they are learning in order to achieve targeted learning goals (Saputra & Marlina, 2020;Suwartiningsih, 2021). This explains that differentiated learning is creating a class that has diversity by providing opportunities for students to obtain content, process ideas and improve the learning outcomes of each student so they can learn more effectively (Faiz et al, 2022;Miqwati et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…One effort that can be made to overcome this problem is by implementing a differentiated learning model. Differentiated learning is a way of teaching that pays attention to students' differences in interests, talents and learning styles to bring diversity to the classroom (Pitaloka & Arsanti, 2022;Saputra & Marlina, 2020). Apart from that, the meaning of differentiated learning also includes adapting learning to students' interests, learning preferences, and readiness to improve learning outcomes (Aprima & Sari, 2022;Avivi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A positive, supportive, and inclusive class culture must be created. Teachers provide ongoing feedback and support to students, addressing individual strengths and aspects that need improvement (Saputra, 2021). Technique scaffolding and small group teaching can be implemented to help students achieve learning objectives (Waliyudin et al, 2022).…”
Section: Differentiated Learning Implementation Strategymentioning
confidence: 99%
“…Differentiated learning also has an impact on students' concentration levels. Research by Saputra (2021) shows that implementing differentiated learning increases students' learning concentration at SDN 17 Jawa Gadut, Padang. This is in harmony with what was revealed by Marlina et al (2023), who found that differentiated learning effectively improves concentration and learning outcomes in students with diverse learning needs.…”
Section: The Effectiveness Of Differentiated Learningmentioning
confidence: 99%